Revisiting Hayek's political economy - Boettke, Peter J.; Storr, Virgil Henry, 1975- (Bingley, U.K. : Emerald, 2016)
Advances in Austrian Economics is a research annual whose editorial policy is to publish original research articles on Austrian economics. Each volume attempts to apply the insights of Austrian economics and related approaches to topics that are of current interest in economics and cognate disciplines. Volume 21 exemplifies this focus by highlighting key research from the Austrian tradition of economics with other research traditions in economics and related areas.
Hayek's Nobel / Bruce Caldwell -- F.A. Hayek and the rationality of individual choice / Mario J. Rizzo -- Hayek and contemporary macroeconomics / Lawrence H. White -- Hayek enriched by complexity enriched by Hayek / Robert L. Axtell -- Constitutionalism, federalism and limited government: Hayekian arguments in political scientists' perspective / Viktor J. Vanberg -- Hayek's political insights: emergent orders and laid on laws / Michael C. Munger -- Why Hayek matters: the epistemic dimension of comparative institutional analysis / Peter J. Boettke, Vlad Tarko, Paul Aligica.
Includes bibliographical references.
Print version record
Keywords: Hayek, Friedrich A. von -- 1899-1992.; Business & Economics -- Economics -- Macroeconomics; Econometrics; Economics -- History -- 20th century; Austrian school of economics -- History